Measurements of spatial correlations in quantum gases using ultralong-range strontium Rydberg molecules. Issue 12 (January 2020) - Whalen, J D; Ding, R; Kanungo, S K; Dunning, F B; Killian, T C; Yoshida, S; Burgdörfer, J
Synopsis: The photoexcitation of ultralong-range Rydberg molecules is demonstrated as a probe of spatial cor-relations in a quantum gas on previously inaccessible length scales of 1400-3200 a 0 . Measurements using cold (∼1 μK) (fermionic) 87 Sr and (bosonic) 84 Sr reveal the effects of quantum statistics on the pair correlation function g (2) ( R ).